Disability, disaster management and the law in Nigeria (2018)
A strong link exists between disaster and disability. Disasters frequently cause disabilities for persons who had none and worsen or cause additional disabilities for persons with disabilities (PWDs). PWDs are usually more at risk in the event of a life- threatening human induced disaster such as bomb explosion or natural disasters like earthquake, tsunami, landslide. Disasters can lead to harm that can be prevented or reduced by including disability in disaster management. PWDs are disproportionately represented among casualties of disaster due to failure to mainstream disability in disaster risk reduction programmes. Incidental or charitable intervention for PWDs in the event of disaster needs to be replaced by a right-based approach to disaster risk management, which mainstreams disability and the peculiar needs of PWDs. While disaster management should cover all segments of society, PWDs are viewed as recipients of charity rather than subjects of rights. Article 11 of the CRPD provides for the right of PWDs to all available measures which the state should provide, to ensure protection and safety of PWDs in situations of risk, including armed conflict, humanitarian emergencies and the occurrence oj natural disasters. This chapter discusses the intersections between disability and disaster management in Nigeria. It focuses on PWDs and disaster, due to the high number of persons affected by disability either as PWDs or as caregivers, the existing level of discrimination against PWDs in access to social benefits, as well as the potential of disasters to either aggravate disability or increase the number of PWDs by causing injuries, damages, displacements, health hazards due to poor hygiene, food and water shortages. The paper concludes with recommendations including the need to mainstream disability in disaster management plans, implementation and post disaster recovery activities, reflecting the principles of equality and non-discrimination in all disaster management programmes, enacting disaster management laws at all levels, creating awareness and preparedness drills for everyone, and for PWDs in the language that they understand, like Braille and sign language